White and dark layer formation mechanism in hard cutting of AISI52100 steel. (April 2018) - Zhang, Fang-yuan; Duan, Chun-zheng; Wang, Min-jie; Sun, Wei
Abstract: White and dark layers formed in hard cutting a workpiece have a great influence on the distribution of residual stress and performance of the workpiece. Orthogonal cutting of AISI 52100 steel with PCBN inserts was employed, and the microstructure, phase components, carbon distribution, and hardness of the white and dark layers were analyzed via scanning electron microscopy, X-ray diffraction, electron probe microanalysis, nanoindentation, and transmission electron microscopy. The results demonstrate that the white layer is formed by a rapid austenite transformation and quenching process, and the dark layer is formed by a tempering process. Plastic deformation promotes the austenite transformation of the white layer and the tempering process of the dark layer and plays a role in the grain refinement of both the white and dark layers. The rapid heating process produced by the cutting process causes the austenite transformation and increases the nucleation rate of austenite. The plastic deformation provides the phase transformation driving force, which can accelerate the formation of the white layer. Meanwhile, defects such as dislocations formed owing to plastic deformation refine the subgrains in the white layer. The heat that transfers into the subsurface and the stress induced by the plastic deformation provide the driving force for dynamic recovery and dynamic recrystallization in the dark layer; the subgrains in the dark layer are segmented by dislocation motion.